The Influence of Competence, Satisfaction and Organizational Climate on Nurse Performance - Srigede, Lalu Wirawan; Menap, Menap; Karjono, Karjono (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nurses are at the forefront of health services through providing nursing care. The facts in the field of implementing Nursing Care Standards according to standards are often ignored, nurses often do not carry out their main duties and functions according to competence because they have to carry out work that is not within their competence, on the other hand, nurse dissatisfaction arises because of a mismatch between services and work. This study aims to analyze the influence of competency, satisfaction and organizational climate on the performance of nurses at the West Lombok Regency Health Center to explore the impact of competency, job satisfaction and organizational climate on the performance of nurses at the West Lombok Regency Health Center. A quantitative approach was used involving 83 nurse respondents, and data was collected through questionnaires that had been tested for validity and validity reliability which covers these aspects. Data analysis was carried out using univariate, bivariate statistical techniques with Chi-Square, and multivariate with Logistic Regression. The research results show a beta value of 1.735 with a significance value of 0.012. The significant influence of the job satisfaction variable on nurse performance can be seen from the research results which show a beta value of 1.116 with a significance value of 0.006, a beta value of 2.350 with a significance value of 0.000, indicating a significant influence of the organizational climate variable on nurse performance. Thus, organizational climate is identified as the dominant variable that influences the performance of nurses at the West Lombok Regency Community Health Center.